2019
DOI: 10.1007/s00784-019-03008-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enamel matrix derivative on wound healing following gingival recession coverage using the modified coronally advanced tunnel and subepithelial connective tissue graft: a randomised, controlled, clinical study

Abstract: Objectives The potential effect of enamel matrix derivative (EMD) on wound healing following recession coverage surgery is still controversially discussed in the literature. The aim of this randomised, controlled, single blinded clinical study was, therefore, to investigate clinically and immunologically the potential effects of EMD on early wound healing and clinical results following treatment of single and multiple gingival recessions by the modified coronally advanced tunnel technique (MCAT) and subepithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
12
21
0
Order By: Relevance
“…The abovementioned differences were not statistically significant. These outcomes compare well with those reported by other studies, where MCAT was used [10,12,23,24], and are consistent with the conclusion of a recent systematic review and meta-analysis [8]. Consequently, the tunnel approach was found to be highly effective in treatment of multiple GR, exhibiting an overall root coverage of 87.9%, in addition to CRC of 57.5%.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The abovementioned differences were not statistically significant. These outcomes compare well with those reported by other studies, where MCAT was used [10,12,23,24], and are consistent with the conclusion of a recent systematic review and meta-analysis [8]. Consequently, the tunnel approach was found to be highly effective in treatment of multiple GR, exhibiting an overall root coverage of 87.9%, in addition to CRC of 57.5%.…”
Section: Discussionsupporting
confidence: 90%
“…Cheng et al [26] performed meta-analysis and concluded that higher PPD reduction tends to occur when EMD was used additionally to SCTG. However, written evidence that took a comparative approach to efficacy of analyzed treatment modalities is rather scarce and only one study was found to compare clinical outcomes following treatment of Miller class I, II, or III recessions by means of MCAT+SCTG combined with and without EMD [12]. At 6 months, ARC measured 78 ± 26% in the test group and 77 ± 18% in the control group, while mean GR was 0.9 ± 1.3 mm and 1.0 ± 1.0 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modi ed coronally advanced tunnel in combination with subepithelial connective tissue graft used in this study showed successful root coverage at 1-year post-op. This is consistent with other publications [7,28], showing a high degree of root coverage of Miller I and II gingival recession. With the help of three-dimensional measurement, the present study found that the gingival HG, AG, VG and MTG were signi cantly higher at 2 weeks after surgery than baseline.…”
Section: Discussionsupporting
confidence: 93%